O papel da inovação aberta na internacionalização de empresas em rede - Grieco, Antonio Augusto de Miranda (2012)
This study combines two current issues: the internationalization of business and innovation. The aim of this work is to study the relationship between innovation activities, especially open innovation and network internationalization. The methodology is qualitative and analyzes the relationships between the processes of internationalization of firms in open innovation network. The management of innovation in companies go beyond the concept of technological innovation and building international networks are important as provision of competitive advantage for a company to operate in various foreign markets. This research aims to contribute to enhancing understanding of relations between these two contemporary phenomena, the internationalization of business and innovation.